Bibliometric Analysis of Trends in Research on Communication Apprehension - Marcus Gee Whai, Kho; Su Hie, Ting (Universiti Putra Malaysia Press, 2025)
The bibliometric analysis examined communication apprehension (CA) research trends by analysing 204 articles from the Scopus database published between 2013 and 2022. There was a substantial increase in CA publications after 2021, following a period of stability from 2017 to 2020. The majority of the publications were in English. Most of the publications on CA are in the social sciences. Transdisciplinary studies are on the rise, with researchers investigating CA in computer mediated communication in online settings and different cultures. Universiti Teknologi Malaysia was at the forefront of university contributions, while the United States had a dominant position on a global scale. The network map shows collaboration between scholars from the United States, Malaysia, Turkey, Thailand, and Taiwan. McCroskey and Richmond are leading researchers in CA, while Arquero is inclined towards co-publications. CA research is most frequently published in PLOS One, Communication Education, and Computers in Human Behaviour. Constraints encompassed dependence on Scopus, restricted search words, and difficulties with citation analysis. Subsequent investigations should utilise a variety of methodologies and databases and concentrate on implementing interventions and longitudinal studies on CA.